Chemical Content and In Vitro Digestibility of Broiler Litter Fermented at Different Ripen Time - Marry Christiyanto; Cahya Setya Utama (Indonesian Center for Animal Research and Development (ICARD), 2022)
The aim of this study was to examine effect of length of chicken litter fermentation on chemical content and in vitro digestibility. Completely randomized design was applied in this study with 4 treatments and 4 replications. The treatments were T0 = no fermentation; T1 = fermentation of chicken litter for 3 weeks; T2 = fermentation of chicken litter for 6 weeks; and T3 = fermentation of chicken litter for 9 weeks. Parameters observed were chemical content and digestibility value of fermented chicken litter. Different fermentation time affected the chemical content of fermented chicken litter, namely water, fat, BETN and TDN content, but did not affect ash content and fiber content. Different fermentation time affected dry matter, protein, fiber fraction digestibility (ADF, NDF, Hemicellulose), but did not affect organic matter digestibility, VFA concentration, NH3 concentration and total protein production of chicken litter. Based on dry matter, ADF, NDF hemicellulose digestibility and VFA concentration, it is concluded that recommended ripen time for chicken litter fermentation is 6 weeks.